Molecular Docking Study of Phenolic Compounds from the Ethanolic Extract of Olive Leaves (Olea europaea L.) as Potential Treatment for Preeclampsia - Yetti Anggraini; Yuliawati Yuliawati (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Preeclampsia is a pregnancy-related disorder characterized by hypertension and proteinuria and is closely associated with oxidative stress, inflammation, endothelial dysfunction, and apoptosis. Olive leaves (Olea europaea L.) are rich in phenolic compounds with well-documented antioxidant and anti-inflammatory properties, making them a promising source of natural therapeutic agents. This study aimed to evaluate the potential of phenolic compounds from the ethanolic extract of olive leaves as candidates for treating preeclampsia using a molecular docking approach. The two-dimensional structures of selected phenolic compounds, including kaempferol, luteolin, and oleuropein, were obtained from the PubChem database and prepared as ligands. Target proteins associated with the pathophysiology of preeclampsia were prepared using AutoDock Tools by removing water molecules and separating native ligands. Molecular docking simulations were conducted to analyze binding affinities and interaction patterns between the phenolic compounds and the target proteins. The results demonstrated that all tested compounds exhibited favorable binding energies and formed stable interactions with key amino acid residues at the active sites of the target proteins. Among the compounds evaluated, oleuropein showed the strongest binding affinity, followed by luteolin and kaempferol. These findings suggest that phenolic compounds from the ethanolic extract of olive leaves have potential as therapeutic agents for preeclampsia, possibly through antioxidant and anti-inflammatory mechanisms. However, further in vitro and in vivo studies are required to validate these computational findings and confirm their biological efficacy.